Transimpedance amplifier with a compression stage for wide dynamic range optical applications. Issue 7 (July 2015) - Atef, Mohamed
Abstract A high dynamic input transimpedance amplifier was implemented in 130 nm CMOS technology. The proposed TIA is an inverter with a diode connected NMOS and a gate controlled PMOS loads which is cascode connected with the inverter. The square law compression NMOS increases the input photocurrent up to 10 mA. The TIA has an integrated input referred noise current of 135 nA, 227 MHz bandwidth. The TIA shows a transimpedance gain of 59 dBΩ and a 97 dB dynamic range. The TIA consumes 2.3 mA from 1.5 V voltage supply.